Intervention Effect of Oropharyngeal Administration of Colostrum in Preterm Infants: A Meta-Analysis - Huo, Mengyue; Liu, Chunli; Mei, Hua; Zhang, Yuheng; Liu, Chunzhi; Song, Dan; Zhang, Yayu; Zhang, Yanbo; Xin, Chun (Frontiers in Pediatrics, 2022)
OBJECTIVE:To evaluate the efficacy and safety of oropharyngeal administration of colostrum (OAC) in preterm infants. METHODS:We searched Embase, MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL) and website of the clinical trials, search time from the establishment of the databases or websites up to Feb 1, 2022. Collect Randomized controlled trials (RCTs) of comparing OAC vs. placebo or no intervention in preterm infants (gestation age ≤32 weeks or birth weight ≤1500 g). Two researchers independently screened the literature, extracted the data and evaluated the quality of the literature, and adopted Review Manager 5.3 software for meta-analysis. RESULTS:Eleven RCTs (n = 1173) were included in the review. Meta-analysis showed significant difference in the incidence of necrotizing enterocolitis (NEC) (P = 0.009, RR = 0.51, 95% CI = 0.31-0.84), Late-onset sepsis (LOS) (P = 0.02, RR = 0.75, 95% CI = 0.59–0.95), ventilator-associated pneumonia (VAP) (P = 0.03, RR = 0.48, 95% CI = 0.24–0.95), the time to reach full enteral feeds (P <0.00001, MD = -3.40, 95% CI = -3.87– -2.92), duration of hospital stay (P <0.00001, MD = -10.00, 95% CI = -11.36– -8.64) and the rate of weight gain (kg.d) (P <0.00001, MD = 2.63, 95% CI = 2.10– 3.16) between the colostrum group and control group. Meanwhile, researchers found no signifificant differences between the colostrum group and control group in the incidence of bronchopulmonary dysplasia (BPD) (P = 0.17, RR = 0.83, 95% CI = 0.64–1.08), intraventricular hemorrhage (IVH) (grade ≥3) (P = 0.05, RR = 0.44, 95% CI = 0.19–1.01), periventricular leukomalacia (PVL) (P = 0.67, RR = 0.70, 95% CI = 0.14–3.49), retinopathy of prematurity (ROP) (P = 0.29, RR = 1.25, 95% CI = 0.82–1.89) and patent ductus arteriosus (PDA) (P = 0.17, RR = 1.22, 95% CI = 0.92–1.62). CONCLUSION:OAC can reduces the incidence of NEC, LOS and VAP in preterm infants, shortening time to reach full enteral feeds and duration of hospital stay, increasing the rate of weight gain (kg.d). Therefore, OAC can be used as part of routine care for preterm infants.